Aplicação da vacina hepatite B na região ventroglútea: avaliação da reação álgica em recém-nascidos - Gonçalves, Paula Alencar (2020)
Introduction: The object of this study is the evaluation of the pain reaction caused by the application of the Hepatitis B vaccine in the Ventrogluteal Region in newborns. This vaccine is administered intramuscularly by the nursing team in the vastus lateralis region, preferably in the first 12 hours of life. Considering that the literature for 60 years points to the ventrogluteal region as the safest for intramuscular injections and that research demonstrates that the use of this site provides equal immunogenicity and less local reactogenicity, with less pain, has the Purpose: to analyze the pain reaction produced by the application of the Hepatitis B vaccine in the ventrogluteal region in newborns. Methodology: Quantitative, exploratory cross-sectional study, carried out in the joint accommodation of a university hospital. The population was composed of 121 newborns. The study was approved by the Research Ethics Committee under opinion número 3.606.133. For analysis of the pain reaction, the NIPS scale was applied and the heart rate was measured before and during the vaccination, as well as the crying time was measured. The data were entered into Microsoft Office Excel and Bioestat 5.0. To describe the data, the following measures were used: minimum, maximum, median, mean, standard deviation, Spearmam's correlation coefficient and for the analytical field, the Mann Whitney and Kruskal Wallis test was used. Results: It was evidenced that the majority of newborns, although they were comfortable before vaccination, presented pain during the procedure, with an average score calculated by the NIPS scale of 2.87 (absence of pain) before and 6.14 (presence pain) during, being considered statistically significant (p <0.0001). A weak positive correlation was identified between HR and NIPS pain scores and a strong correlation between NIPS and crying time. Conclusion: It was found that the pain reaction even with the use of the ventrogluteal region is a reality expressed by high NIPS scores, increased heart rate during the procedure and by the time of crying, and that there is no variation according to the studied characteristics of the newborns.